Social Media and Social Class. (August 2018) - Yates, Simeon; Lockley, Eleanor
Background: This article explores the relationship between social class and social media use and draws on the work of Pierre Bourdieu in examining class in terms of social, economic, and cultural capital. The article starts from a prior finding that those who predominantly only use social media formed a higher proportion of Internet users from lower socioeconomic groups.Data: The article draws on data from two nationally representative U.K. surveys, the OfCom (Office of Communications) Media Literacy Survey ( n ≈ 1, 800 per annum) and the Department of Digital, Culture, Media and Sport's Taking Part Survey ( n ≈ 10, 000 per annum).Methods: Following Yates, Kirby, and Lockley, five types of Internet behavior and eight types of Internet user are identified utilizing principal components analysis and k -means clustering. These Internet user types are then examined against measures of social, economic, and cultural capital. Data on forms of cultural consumption and digital media use are examined using multiple correspondence analysis.Findings: The article concludes that forms of digital media use are in correspondence with other social, cultural, and economic aspects of social class status and contemporary social systems of distinction.